Quality of Life Analysis of HPV-Positive Oropharyngeal Cancer Patients in a Randomized Trial of Reduced-Dose Versus Standard Chemoradiotherapy: 5-Year Follow-Up - Takahashi, Mai; Hwang, Michael; Misiukiewicz, Krysztof; Gupta, Vishal; Miles, Brett A.; Bakst, Richard; Genden, Eric; Selkridge, Isaiah; Botzler, John; Virani, Vruti; Moshier, Erin; Bonomi, Marcelo R.; et al. (Frontiers in Oncology, 2022)
Background Human papillomavirus-positive oropharyngeal carcinoma (HPVOPC) portends a more favorable prognosis compared to environmentally related oropharynx cancer (EROPC). Patients with HPVOPC may be overtreated and endure unnecessary long-term toxicities. Methods Patients with untreated locally advanced HPVOPC received induction chemotherapy with docetaxel, cisplatin, and 5-fluorouracil (TPF) and were randomized to standard chemoradiotherapy (sdCRT) (70 Gy) or reduced-dose chemoradiotherapy (rdCRT) (56 Gy) with weekly carboplatin. Patients were followed for changes in five validated quality of life (QoL) surveys: MD Anderson Dysphagia Inventory and Symptom Inventory for head and neck cancer (MDADI, MDASI-HN), Xerostomia Questionnaire (XQ), and European Organization for Research and Treatment of Cancer Questionnaire (EORTC) with head and neck module (EORTC HN). The secondary endpoints of this study were 5-year progression-free survival (PFS) and overall survival (OS). Results Twenty patients were enrolled and randomized to rdCRT (n = 12) or sdCRT (n = 8). Median follow-up was 88 months. At 5 years, difference in QoL changes all favored the rdCRT arm and two QoL scales reached statistical significance (EORTC global health score: 11.49 vs. -23.94, P = 0.014; EORTC symptom scale: -7.76 vs. 15.19, P = 0.015). The 5-year PFS and OS were 87.5% and 83.3% for sdCRT and rdCRT, respectively. Conclusions Therefore, rdCRT after TPF in HPVOPC is feasible in accordance with the earlier results of the Quarterback Trial and long-term follow-up. These limited results are more favorable in specific QoL domains compared to those of sdCRT and demonstrate equivalent long-term survival. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT01706939, The Quarterback Trial [NCT 01706939].